2019
DOI: 10.1103/physrevb.99.134445
|View full text |Cite
|
Sign up to set email alerts
|

Transient response of the cavity magnon-polariton

Abstract: The Rabi oscillations of a coupled spin-photon system are experimentally studied using time domain microwave transmission measurements. An external magnetic bias field is applied to control the amplitude and frequency of Rabi oscillations, which are a measure of the coherent spin-photon energy exchange and coupling strength respectively. The amplitude and frequency control is described in the time domain as the transient response of a two-level spin-photon system. This approach reveals the link between steady … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The excitation, and therefore the energy, periodically oscillates between cavity and magnon. Hence, the system displays classical magnon-Rabi oscillations [2,22]. Figures .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The excitation, and therefore the energy, periodically oscillates between cavity and magnon. Hence, the system displays classical magnon-Rabi oscillations [2,22]. Figures .…”
Section: Introductionmentioning
confidence: 96%
“…These spectroscopic measurements, however, are performed under continuous driving, and while they have yielded great physical insight into these hybrid systems, flexible and universal information processing requires the manipulation of such physical * tim.wolz@kit.edu † martin.weides@glasgow.ac.uk states on demand and on nanosecond timescales. Despite this necessity for fast manipulation, the literature about time resolved experiments with either an yttrium iron garnet (YIG) waveguide [20] or CMPs [2,7,21,22] is scarce and confined to cavity-pulsing. A simultaneous and coherent control over both subsystems has yet to be demonstrated, which is the subject of this work.…”
Section: Introductionmentioning
confidence: 99%
“…Cavity magnonic systems have attracted significant attentions recently [12][13][14][15][16][17][18][19][20][21][22][23] due to the strong interaction between magnon excitations and microwave photons. Previous studies have demonstrated magnon-photon strong coupling in various resonant microwave systems, such as copper 3-dimentional (3D) cavities [14][15][16][17][18] and coplanar microwave circuits [19,20,24].…”
Section: Introductionmentioning
confidence: 99%
“…At ω c = ω m , C 11 = C 12 = 1/2 and τ + = τ − . Therefore a complete extinction in the |S 21 | 2 -t spectrum is observed, resulting in an equal energy distribution between the spin and photon subsystems 106.…”
mentioning
confidence: 99%